Successful Study for Degrees, 3rd edition - Rob, Barnes (Routledge, 2020)
Thisis a practical guide to studying more effectively at first and higher degree levels. Primarily for students looking for more than just a basic study skills book, it blends practical ideas with sound principles to offer a readily accessible, handy guide.